Parametric Analysis of WEDM to Optimize Cutting Parameters for Inconel 800. (2020) - Deb, Payel; Dutta, Prasenjit; Choudhuri, Bikash; Deoghare, Ashish B.
Abstract: The intent of the current research is to investigate the effect on cutting speed, average surface roughness, total surface roughness, kerf width and wire consumption for Inconel 800 by varying peak current (IP), pulse on time (Ton ) and pulse off time (Toff ) of wire electrical discharge machining. It has been observed from analysis of variance that Ton has highest impact on all the responses followed by Toff and IP. The mathematical models established are found reliable representatives of the experimental results with prediction errors approximately ±5 %. Grey relational analysis has been used to optimize the multi-objective process parameters. The optimal performance has been obtained for Ton 105 (0.35µ s), Toff 35 (11.5 µ s) and peak current 200 A